Thermoacoustic engine as waste heat recovery system on extended range hybrid electric vehicles. (1st July 2020) - Bou Nader, Wissam; Chamoun, Joy; Dumand, Clément
Highlights: Study assesses thermoacoustic waste heat recovery system. A methodology to optimize the overall efficiency of the combined was proposed. Three different thermoacoustic configurations were considered. Fuel savings compared to internal combustion engine are simulated on extended range hybrid electric vehicle. Up to 7.6% of fuel consumption reduction is observed with the three-stage thermoacoustic machine system. Abstract: Waste heat recovery (WHR) systems suggest a promising solution for reducing vehicle CO2 emissions in order to meet the CAFE targets by 2025. This paper presents a methodology to improve the overall efficiency of a combined cycle machine consisting of a reciprocating internal combustion engine (ICE) coupled to a thermoacoustic (TAE) machine used for thermal-to-electric WHR. It investigates the potential of calibrating the ICE at some specific points of its engine map in order to achieve an optimal overall efficiency when coupled to the bottoming thermoacoustic cycle. A three-cylinder gasoline engine is modeled using GT suite code and the effect of spark timing delay on exhaust temperature, exhaust flow and engine brake efficiency are compared to real engine test bench values. Three bottoming thermoacoustic configurations coupled to this ICE are modeled and calibrated according to test results performed on a thermoacoustic machine prototype. The resulting electrical power recovery from the exhaust gas is analyzed and assessed. A Range Extender Hybrid Electric Vehicle (EREV) is considered and fuel consumption is simulated on the WLTC. The results revealed an added value for adding a multi-module TAE in series, to optimize heat recovery with a potential of consumption reduction up to 7.6%. Results have also shown interest in delaying the ignition, enabling higher exhaust temperature and mass flow rate which tend to positively impact the TAE machine. The proposed method is also beneficial in the way that it avoids knocking problems and enables the future design of higher compression ratio engines for auxiliary power unit on EREV.